Women and rights: The category of “gender” as a constitutional guarantee and the gender perspective as a legal methodology - Torres Díaz, María Concepción (2019)
Data on violence against women in Spain are unbearable for an advanced democratic state, which allows inferring that there is a social/sexual reality prior to the social coexistence pact that is discriminatory for women and threatens their fundamental rights. This reality of preexisting subordination to the norms of social coexistencehas been based (and sustained) on the asymmetry of socio/sexual power that pivots in the sex/gender system. Hence the need to provide the “gender” category with constitutional relevance.